Lepidium meyenii biological activity and future perspectives - Zoya Dzhakova; Diana Karcheva-Bahchevanska; Stanislava Ivanova (Makedonsko Farmacevtski Bilten)
Lepidium meyenii Walp. (Brassicaceae) is a plant native to the Andean region. It is also known as Maca and Peruvian ginseng and is considered to have been used in traditional medicine for more than 2000 years. Lepidium meyenii is regarded as a plant adaptogen. Nowadays, Maca root is used worldwide as a food, tonic, antioxidant, enhancer of fertility, etc. The main compounds in the underground part of the plant are glucosinolates, thiohydantoins, isothiocyanates, macamides, macaene, fatty acids, polysaccharides, alkaloids, fiber, lipids and proteins, which are responsible for various biological activities including antimicrobial, antioxidant, cytotoxic, anti-inflammatory and immunomodulatory activities. The purpose of this review is to summarize the data of some in vitro, in vivo and clinical studies on the biological activity of Maca and to analyze the future perspectives for the inclusion of Maca into novel herbal medicines